EFEKTIVITAS PENERAPAN SISTEM INFORMASI PENGELOLAAN KEUANGAN DAERAH (SIPKD) TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH - Siska Yulia Defitri (Politeknik Raflesia Press, 2022)
Application of information systems at government agencies in particular, is quite an important role in producing high quality financial statements. The government is trying to realize the excellent service to the community by building information technology in the field of finance or accounting in relation to ​​financial Management, namely Financial Management Information System (SIPKD). The purpose of this study was to determine the influence of Implementation Effectiveness of Financial Management Information System (SIPKD) on the Quality of Financial Statements. This research was conducted at the regional work units (SKPD) within the City of Solok the number SKPD 41 units. The sample used in this study as many as 44 people SIPKD operator. Quantitative analysis techniques and simple regression analysis is used as a data analysis technique. The analysis showed the effectiveness of the implementation SIPKD significant effect on the quality of financial reporting in the City in Solok